The Dynamics of Adoption: Theoretical Perspectives and Practical Insights from the Routledge Handbook of Adoption - Adámi-Rózsa, Zsanett (Filológia.hu, 2025)
Adoption research is multifaceted, bridging disciplines such as sociology, psychology and policy studies. While it is not rigid or impossible to cross the lines, separating research traditions, adoption research has often taken two parallel paths, each driven by distinct interests and methodologies. One primary focus is the exploration of best policies and practices for child placement aimed at ensuring stable adoptions and fostering the well-being of all family members. Researchers examine how children and adoptive parents are matched, the satisfaction levels of adoptive families with services, and how these factors influence the length and success of placements. Another significant area of adoption research is developmental psychology. This branch delves into the mental health of adoption minors, their developmental progress after adoption from institutional settings, and their adoption following foster care placements. Since 2000, much of the research has shifted toward understanding the underlying processes affecting adoption outcomes. This includes examining how adoptive parents react to and navigate their roles, as well as the diversity in their communication styles, which profoundly impact adoptees’ adoption and identity formation. Recognising individual differences in adaptation and their root causes is vital for advancing adoption practices. This paper offers a theoretical overview of adoption-related theories and research, as presented in the comprehensive Routledge Handbook of Adoption (2021).